Management of gastrointestinal haemorrhage. Issue 915 (1st January 2002) - Ghosh, S; Watts, D; Kinnear, M
Abstract : A variety of endoscopic haemostatic techniques have enabled major advances in the management of not only bleeding peptic ulcers and bleeding varices, but also in a variety of bleeding lesions in the small intestine and in the colon. Indeed, the development and widespread implementation of endoscopic haemostasis has been one of the most important developments in clinical gastroenterology in the past two decades. An increasingly ageing cohort of patients with multiple co-morbidity are being treated and therefore improving the outcome of gastrointestinal bleeding continues to pose major challenges.